Generation of human TMEM16F-specific affibodies using purified TMEM16F - Kim, Eunyoung; Bang, Jinho; Sung, Ji Hye; Lee, Jonghwan; Shin, Dae Hwan; Kim, Sunghyun; Lee, Byoung-Cheol (Frontiers in Molecular Biosciences, 2024)
TMEM16 family proteins are involved in a variety of functions, including ion transport, phospholipid scrambling, and the regulation of membrane proteins. Among them, TMEM16F has dual functions as a phospholipid scramblase and a nonselective ion channel. TMEM16F is widely expressed and functions in platelet activation during blood clotting, bone formation, and T cell activation. Despite the functional importance of TMEM16F, the modulators of TMEM16F function have not been sufficiently studied. In this study, we generated TMEM16F-specific affibodies by performing phage display with brain-specific TMEM16F (hTMEM16F) variant 1 purified from GnTi -cells expressing this variant in the presence of digitonin as a detergent. Purified human TMEM16F protein, which was proficient in transporting phospholipids in a Ca 2+ -dependent manner in proteoliposomes, was coated onto plates and then the phage library was added to fish out TMEM16F-binding affibodies. As a result, the full sequences of 38 candidates were acquired from 98 binding candidates. Then, we selected 10 candidates and purified seven of them from E. coli expressing these candidates. Using ELISA, bio-layer interferometry, and size exclusion chromatography, we confirmed that two affibodies bound to human TMEM16F with high affinity.These affibodies can be useful for therapeutical and diagnostic applications of TMEM16F-related cancer and neurodegenerative diseases. Future studies will be required to investigate the effects of these affibodies on TMEM16F function.